To investigate the tumor promotion role of PLOD3 in colorectal cancer and its potential as a prognostic biomarker and therapeutic target - Wanhui Dong; Su Li; Wei Tang; Qingming Sun; Pei Zhu; Mingxing Wang; Bin Xu (Scientific Reports, 2025)
Abstract PLOD3 (procollagen-lysine, 2-oxoglutarate 5-dioxygenase 3), a key enzyme involved in collagen post-translational modification, is critical for maintaining the structural integrity of the extracellular matrix (ECM). Dysregulation of PLOD3 has been implicated in various malignancies, including colorectal cancer (CRC).This study aimed to elucidate the role of PLOD3 in CRC and evaluate its potential as a prognostic biomarker and therapeutic target. We conducted a comprehensive analysis utilizing data from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) to evaluate PLOD3 expression in CRC. Univariate and multivariate Cox regression analyses were conducted to investigate its impact on overall survival. Functional assays, including wound healing, Transwell migration, and invasion assays, were carried out in CRC cell lines with modified PLOD3 expression to elucidate its role in regulating tumor cell behavior. Furthermore, Gene Set Enrichment Analysis (GSEA) was employed to identify signaling pathways associated with PLOD3 expression. Our findings demonstrate that PLOD3 is significantly overexpressed in CRC tissues compared to normal tissues, and its elevated expression is associated with poor prognosis and reduced overall survival. The study also developed a RiskScore model incorporating PLOD3 and 11 other genes, which exhibited strong predictive performance for patient outcomes. Functional experiments confirmed that PLOD3 overexpression enhances CRC cell migration and invasion. GSEA linked high PLOD3 expression to the activation of epithelial-mesenchymal transition (EMT) and metastasis-related pathways. In conclusion, PLOD3 plays a pivotal role in CRC progression by promoting tumor growth and metastasis. Its elevated expression serves as an independent prognostic marker and a potential target for therapeutic intervention, offering new insights into the molecular mechanisms driving CRC.